2009
DOI: 10.1021/jf803579e
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Administration of High Doses of Pterostilbene and Quercetin to Mice Is Not Toxic

Abstract: The aim of this study is to evaluate possible harmful effects of high doses of t-pterostilbene (t-PTER) and quercetin (QUER) in Swiss mice. Mice were fed during 28 days at doses of 0, 30, 300, and 3000 mg/kg body weight/day of t-PTER, QUER, or a mixture of both, t-PTER + QUER, which are equivalent to 5, 50, and 500 times, respectively, the estimated mean human intake of these polyphenols (25 mg/day). Daily oral administration of QUER, t-PTER, or a mixture of both of them did not cause mortality during the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 33 publications
11
119
0
Order By: Relevance
“…In addition, it has been reported that dietary administration of a high dose of PTE produced no toxicity in mice. More specifically, 3,000 mg/kg of body weight/day of PTE for 28 days did not affect biochemical or clinical parameters or the organ weights of the tested mice (71). These findings demonstrated that PTE possesses key preclinical characteristics of a potent antibiofilm agent.…”
Section: Met14mentioning
confidence: 73%
“…In addition, it has been reported that dietary administration of a high dose of PTE produced no toxicity in mice. More specifically, 3,000 mg/kg of body weight/day of PTE for 28 days did not affect biochemical or clinical parameters or the organ weights of the tested mice (71). These findings demonstrated that PTE possesses key preclinical characteristics of a potent antibiofilm agent.…”
Section: Met14mentioning
confidence: 73%
“…Multiple studies demonstrate that chronic administration of dietary flavonols, at concentrations as high as 3,000 mg/kg, has no significant toxicity in animal studies (39)(40)(41). Dietary flavonols used in clinical trials have also been well tolerated (41).…”
Section: Figurementioning
confidence: 99%
“…Based on the ratio of surface area (human/ mouse) and the doses of 25, 50 and 100 mg/kg tested in mice of the present study, the corresponding doses in human are 192.3, 384.6 and 769.2 mg/day. Treating mice with up to 3,000 mg/kg quercetin exhibit no toxicity [43]. Twenty-two patients administrated with 500 mg of quercetin twice a day for 4 weeks experience none negative side effects [37].…”
Section: Quercetinmentioning
confidence: 99%